The Individual, Education or Work Environment Influences the Quality of Graduates’ Employment? - Kotsis, Ágnes (International Journal of Engineering and Management Sciences, 2017)
In this paper I examine what has an effect on the quality of the graduated students’ employment. The quality is measured by the the discrepancy between the educational attainment of workers and the educational requirements of their job. On the base of this I can distinguish matching and overeducated workers. The latter category can be divided into two other groups, so called genuinely overeducated, who are not satisfied with their mismatch, and apparently overeducated, who are satisfied with their mismatch. Using multinomial logit model I try to identify those individual, educational and workplace’s characteristics that influence being matching, apparently, or genuinely overeducated using the database of students graduated in 2007 and 2009 in the University of Debrecen. I try to test those factors that were determined in the literature like mobility and commuting propensity, market rigidity, career mobility, job tenure.